Encapsulation Rutin with Chitosan-NATPP Using Coaservation Method - Bambang Cahyono; Meiny Suzery; H Hadiyanto; Sestri Bela Pratiwi (Reaktor, 2017)
Abstract This study aims to make microparticles of rutin compounds at various concentrations with NaTPP-chitosan as matrix. Encapsulation is done by coaservation method. The success of encapsulation was identified by UV-Vis spectrophotometry, Fourier Transform Infra-Red (FTIR) spectroscopy and Scanning electron microscopy (SEM). Based on UV-Vis spectrophotometry analysis, the efficiency of encapsulation (EE) and loading capacity (LC) was obtained at 62,43-94,36 and 1,73% -32,1%, at rutine concentration 0,625-11,25 mM. The success of rutin encapsulation is demonstrated by the rutin characteristics of the product seen with the presence of peaks of aromatic rings, indicating the presence of rutin compounds contained in the chitosan matrix. SEM analysis shows rough and porous surface morphology in microcapsules. The rutin release profile of the microcapsules is described as two phase processes, burst release at the initial discharge in the first 30 min followed by slow release. At the highest LC (11.25 mM concentration), it provides greater discharge rates for both synthetic fluid simulations 77.53 ± 3.59% and 78.76 ± 4.00% after 3h of discharge. The controlled release data showed high discharge rates at acidic pH than alkaline pH. Keywords: Rutin, encapsulation, citosan, coaservation